Transcriptome Analysis of Green and White Leaf Ornamental Kale Reveals Coloration-Related Genes and Pathways - Zhou, Fuhui; Liu, Yang; Feng, Xin; Zhang, Yuting; Zhu, Pengfang (Frontiers in Plant Science, 2022)
Leaf color is a crucial agronomic trait in ornamental kale. However, the molecular mechanism regulating leaf pigmentation patterns in green and white ornamental kale is not completely understood. To address this, we performed transcriptome and pigment content analyses of green and white kale leaf tissues. A total of 5404 and 3605 different expressed genes (DEGs) were identified in the green vs. white leaf and the green margin vs. white center samples. KEGG pathway enrichment analysis showed that 24 and 15 common DEGs in two pairwise comparisons were involved in chlorophyll metabolism and carotenoid biosynthesis, respectively. 17 genes related to chlorophyll biosynthesis were significantly upregulated in green leaf tissue, especially chlH and por. Of the 15 carotenoid biosynthesis genes, all except CYP707A and BG1 were lower expressed in white leaf tissue. Green leaf tissue exhibited higher levels of chlorophyll and carotenoids than white leaf tissue. In addition, the DEGs involved in photosystem and chlorophyll binding proteins had higher expression in green leaf tissue. The PSBQ, LHCB1.3, LHCB2.4 and HSP70 may be key genes of photosynthesis and chloroplast formation. These results demonstrated that green and white coloration in ornamental kale leaves was caused by the combined effects of chlorophyll and carotenoid biosynthesis, chloroplast development, as well as photosynthesis. These findings enhance our understanding of the molecular mechanisms underlying leaf color development in ornamental kale.